X.a.f.s. studies of chicken dicupric ovotransferrin. - Garratt, R C (1991)
A comparison of Cu K-edge x.a.f.s. spectra with that of the equivalent Fe K-edge for chicken ovotransferrin (COT) indicates that the metal ions occupy essentially the same binding sites in the protein. However, in the case of the Cu2+ complex the metal appears to have reduced co-ordination. Changes are observed in the x.a.f.s. of 90%-saturated COT (Cu1.8COT) on freeze-drying. The three-dimensional X-ray structures of rabbit serum transferrin and human lactoferrin have shown that the ferric cations are co-ordinated by four protein ligands and a bidentate carbonate anion in a distorted octahedral arrangement [Anderson, Baker, Dodson, Norris, Rumball, Waters & Baker (1987) Proc. Natl. Acad. Sci. U.S.A. 84, 1768-1774; Anderson, Baker, Norris, Rice and Baker (1989) J. Mol. Biol. 209, 711-734; Bailey, Evans, Garratt, Gorinsky, Hasnain, Horsburgh, Jhoti, Lindley, Mydin, Sarra & Watson (1988) Biochemistry 27, 5804-5812]. This structural information, together with the differences in e.x.a.f.s. spectra for solution and freeze-dried samples of diferric COT [Hasnain, Evans, Garratt & Lindley (1987) Biochem. J. 247, 369-375] suggests that the synergistic carbonate anion may be capable of behaving as a unidentate linkage to the Cu2+ in the dicupric complex. Data for Cu1.8COT are consistent with only three protein ligands bound to Cu2+, monodentate binding of the synergistic anion in one lobe and its bidentate binding in the other lobe. Such flexibility in the anion co-ordination may be a requirement for the uptake and release of metals by the transferrins.